FOXK transcription factors: Regulation and critical role in cancer. (28th August 2019) - Liu, Ying; Ding, Wei; Ge, Hu; Ponnusamy, Murugavel; Wang, Qiong; Hao, Xiaodan; Wu, Wei; Zhang, Yuan; Yu, Wanpeng; Ao, Xiang; Wang, Jianxun
Abstract: Growing evidence suggests that alterations of gene expression including expression and activities of transcription factors are closely associated with carcinogenesis. Forkhead Box Class K (FOXK) proteins, FOXK1 and FOXK2, are a family of evolutionarily conserved transcriptional factors, which have recently been recognized as key transcriptional regulators involved in many types of cancer. Members of the FOXK family mediate a wide spectrum of biological processes, including cell proliferation, differentiation, apoptosis, autophagy, cell cycle progression, DNA damage and tumorigenesis. Therefore, the deregulation of FOXKs can affect the cell fate and they promote tumorigenesis as well as cancer progression. The mechanisms of FOXKs regulation including post-translational modifications (PTMs), microRNAs (miRNAs) and protein–protein interactions are well demonstrated. However, the detailed mechanisms of FOXKs activation and deregulation in cancer progression are still inconclusive. In this review, we summarize the regulatory mechanisms of FOXKs expression and activity, and their role in the development and progression of cancer. We have discussed whether FOXKs act as tumor suppressors/oncoproteins in tumor cells and their therapeutic applications in malignant diseases are also discussed. This review may assist in designing experimental studies involving FOXKs and it would strength the therapeutic potential of FOXKs as targets for cancers. Highlights: FOXKs mediate multiple physiological and pathological processes by inducing transcription of target genes. FOXKs possess double-edged effect on cancer. Deregulation of FOXKs is associated with a series of malignancies. FOXKs are potential targets of chemotherapeutic drugs.